Exploring the Biological Functions and Anti-Melanogenesis of Phallus indusiatus for Mushroom-Based Cosmetic Applications - Kanyanat Theeraraksakul; Kittitat Jaengwang; Kiattawee Choowongkomon; Lueacha Tabtimmai (Cosmetics, 2023)
Phallus indusiatus, or bamboo mushroom, has been reported for its nutraceutical properties, while its cosmeceutical properties remain unclear. In this study, we conducted extractions of whole, fresh P. indusiatus using both aqueous and ethanolic methods. Among the extracts, ultrasonic-assisted extraction method with DI showed the highest antioxidant activity compared to the others. For cosmeceutical assessment, we evaluated the extracts’ inhibitory effects against ECM-degrading enzymes and found that they exhibited a modest inhibitory effect of approximately 50%. Remarkably, ultrasonic-assisted extraction with DI demonstrated promising cosmeceutical properties. Additionally, pressure-assisted extraction with DI showed a potentially protective effect against H2O2-induced DNA damage. To investigate the anti-melanogenic effect on MNT-1 cells, we treated them with the extracts and observed a significant decrease in cellular tyrosinase activity under α-MSH stimulation. This resulted in a relative reduction in melanin content. Notably, autoclaving extraction exhibited a significantly greater anti-melanogenic effect than the other extracts at the lowest concentration tested. Furthermore, the extracts demonstrated a reduction in NO production under LPS-induced inflammation. Hot water extraction with DI and ethanol exhibited a stronger anti-inflammatory effect compared to diclofenac, without any cytotoxicity. These findings highlight the hidden cosmeceutical properties of P. indusiatus and suggest its potential use as a bioactive ingredient in cosmetic formulations.